Reducing Nurses’ Barriers to Reporting Adverse Events Using a WeChat-Based Cognitive Load Training Platform: An Open-Label, Randomized Controlled Trial - Zhao X; Zhao L; Li G; Yang W; Wang H; Yang Y (Risk Management and Healthcare Policy)
Xiaoying Zhao,1 Lihua Zhao,1 Guangyao Li,2 Wenfeng Yang,1 Huili Wang,1 Yanmeng Yang1 1Handan First Hospital, Handan, Hebei, 056002, People’s Republic of China; 2Handan second Hospital, Handan, Hebei, 056001, People’s Republic of ChinaCorrespondence: Lihua Zhao, Nursing Department, Handan First Hospital, 25 Congtai Road, Handan, Hebei, People’s Republic of China, 056002, Tel +8613730081565, Email dyyyhlb2024@163.comObjective: To investigate the effects of a cognitive load theory (CLT)-based WeChat training platform on reducing the barriers to reporting adverse events among clinical nurses.Methods: In total, 400 clinical nurses from a tertiary general hospital were randomized into experimental and control groups (200 each). The experimental group used the CLT-based WeChat training platform, whereas the control group received conventional training for nursing adverse events. Both interventions lasted 12 weeks. Barriers to reporting, reporting awareness, intention, and habit scores were compared between the groups.Results: After the dropouts, 197 experimental and 196 control participants completed the study. In the experimental group, the total scores for barriers to reporting adverse events and in the dimensions of punitive culture, reporting process, and reporting significance scores were 93.87 ± 6.85, 48.88 ± 4.68, 21.53 ± 4.15, and 23.40 ± 2.11, respectively, whereas the control group corresponding scores were 72.07 ± 6.67, 34.20 ± 6.02, 20.06 ± 3.25, and 17.36 ± 2.92, respectively. The experimental group demonstrated significantly higher scores and reporting significance (P all < 0.01). Additionally, the experimental group had significantly higher scores for safety event reporting awareness, intention, and habits than those in the control group (P < 0.01). When responding to nursing adverse events of various severity, the only exception to statistically significant differences between the groups was in “reporting to the head nurse” for medium-severity incidents (P = 0.302). However, the experimental group demonstrated significantly higher rates of “submitting an adverse event report”, “reporting to the head nurse”, and “discussing with colleagues” than those in the control group regardless of the severity of the adverse event (P < 0.01).Conclusion: This study confirmed that the CLT-based WeChat training platform model can effectively reduce the level of barriers to adverse event reporting by nurses, enhance nurses’ adverse event reporting awareness, intention, and promote improvement in nurses’ adverse event reporting behaviors, thereby improving the quality of nursing care and patient safety.Keywords: cognitive load theory, WeChat training platform, nurse, adverse event reporting barriers, patient safety